Extracellular vesicles as antigen carriers for novel vaccination avenues - Mehanny, Mina; Lehr, Claus Michael; Fuhrmann, Gregor (Advanced Drug Delivery Reviews, 2021)
Antigen delivery has always been a challenge in scientific practice of vaccine formulation. Yet, mammalian extracellular vesicles (EVs) or bacterial membrane vesicles (MVs) provide an innovative avenue for safe and effective delivery of antigenic material. They include intrinsically loaded antigens from EV-secreting cells or extrinsically loaded antigens onto pre-formed vesicles. Interestingly, many studies shed light on potential novel anti-cancer vaccination immunotherapy for therapeutic applications from mammalian cell host-derived EVs, as well as conventional vaccination for prophylactic applications using bacterial cell-derived MVs against infectious diseases. Here, we discuss the rationale, status quo and potential for both vaccine applications using EVs.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Antigen; Cancer; Extracellular vesicles; Immunotherapy; Infection; Outer membrane vesicles; Vaccine